Makanan Haram dan Pengaruhnya dalam Kehidupan: Kajian Tafsir Ahkam Surat Al-Māidah Ayat 3-5 - Anshori, Muhammad (Fakultas Syariah dan Ekonomi Islam, IAIN Syaikh Abdurrahman Siddik, Bangka Belitung, 2020)
This paper explains the interpretation of Surah al-Mā’idah verses 3-5 regarding unlawful food and its effect on life. Humans being are living creatures who need to food and drink, so Allah commands them to fulfill their daily lives in a good way. Teh Qur’an has explained several criteria for halal (lawfull) dan haram (ulawfull) foods. As a source of Islamic teachings, the Qur’an must be interpreted appropriately, so that it can be applied in the real life. Al-Qur’an continues to be studied with various methods and approaches untill gives the rises and develop the various the literatures of exegesis. One of the Styles of interpretation that has developed in the history of Islamic thought is the legal interpretation, or what is known with tafsīr aḥkām (legal exegesis/interpretation). Surah al-Mā’idah verses 3-5 is one form of the application of the tafsīr aḥkām (legal exegesis), because it describes some foods that are forbidden. Among the things that are forbidden was carcasses, blood, pork, animal that died from being beaten, died from being strangled, fall from high places, are gored by other animals, and animal that are slaughted in names othe than Allah. Understanding the verses 3-5 of surat Al-Mā’idah has a correlation with modern scientific discoveries so that the Al-Qur’an can be understandood contextually.